Performance Analysis and Proposed Improvement of Walk-In Process at Plasa PQR Lembong Using LFA (Logical Framework Approach) - ADRIAN (NIM: 29106319), RYAN
Customer satisfaction is an important aspect to create the competitive advantage for company including for the company that operate in telecommunication sector like PT. PQR. The customer satisfaction could generate by product quality and service quality that served to customers. Furthermore, the relationship between customer and company applied in any forms of media that could be direct or indirect physically. Plasa PQR has one of the media that customer and company could make some transaction directly and it categorized as Walk-In Process. There some entities that causes customer dissatisfaction in place aspect. The most prominent entity to make the improvement was customer waiting time factor. Therefore, it is important to analyze Walk-In Process system and procedure operated in Plasa PQR Lembong. Analysis should observe the whole data collection and processed precisely to avoid the misinterpretation decision for improvement. Logical Framework Approach (LFA) was model for improvement begins with identification phase, solution offering, and framework development dynamically. This methodology use for service quality improvement with framework has been existed. Data processing would perform with queuing theory approach and simulation approach. Data processing should involve dynamic condition, so the potential existing condition would breakdown before formulate the decision for improvement. Queuing theory method results in statically that the implementation could be assumed had specific distribution pattern. Meanwhile, with using the simulation approach, the dynamic condition could be performed in if-then condition that could present the performance effect. The simulation results based on existing condition, which is has some empty counters operated by server at lunch break, shows that maximum customer waiting time range within 50 minutes until 72 minutes with all potential lunch break scheduling alternatives. The additional number of temporary server during lunch break produces shorter maximum customer waiting time. It performs 27 minutes maximum customer waiting time and 78% level of utility. The utility level aspect should be regarded considering it will effect on quality of service, it necessary to add the number of operated main counters until five units with other temporary server scheduled. The performance result was 14 minutes in maximum customer waiting time and 63% level of utility